2016
DOI: 10.1149/2.0071609jss
|View full text |Cite
|
Sign up to set email alerts
|

Contact Behavior among Vertically Aligned Carbon Nanotube Bumps under Compression for Flexible Multilayer Substrates

Abstract: Vertically aligned carbon nanotubes (VACNTs) are promising candidates as vertical interconnects in multilayer substrates. Therefore, VACNTs were applied to the via structure in a multilayer flexible substrate as flexible bumps by surface activated bonding indeed. During the manufacturing process, VACNT bumps were compressed and deformed by the bonding pressure. In this research, VANCT deformation and structural mechanics were evaluated and analyzed under compression by an indenter. VACNT bumps were compressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…At the bonded interface, VACNTs were bonded almost vertically to the substrate; otherwise, VANCTs above the interface were buckled and folded by the bonding load, as the authors previously reported. 36)…”
Section: Methodsmentioning
confidence: 99%
“…At the bonded interface, VACNTs were bonded almost vertically to the substrate; otherwise, VANCTs above the interface were buckled and folded by the bonding load, as the authors previously reported. 36)…”
Section: Methodsmentioning
confidence: 99%